Repurposing a Smartwatch to Support Individuals With Autism Spectrum Disorder: Sensory and Operational Considerations. Issue 4 (December 2021) - O'Brien, Amanda M.; Schlosser, Ralf W.; Yu, Christina; Allen, Anna A.; Shane, Howard C.
Smartwatches may provide a natural, portable, and unobtrusive strategy by which to support directive-following for individuals with autism spectrum disorders (ASD). A mentor can send visual supports (e.g., photographs, videos, text) "just-in-time" (JIT) to a learner's smartwatch. This may reduce the need for extraneous face-to-face intervention within social and educational settings and thereby preserve the naturalness of interactions for individuals with ASD. In this article, the following questions are explored: (1) Will some children with ASD with limited functional speech tolerate wearing a smartwatch after receiving only spoken instructions? (2) Can children with ASD who did not initially tolerate wearing a smartwatch increase their tolerance for wearing a smartwatch after they view video models within a visual schedule? and (3) Will children with ASD who tolerate wearing a smartwatch attend to, and follow, scene cue text messages received on the watch? Results provide preliminary evidence for the feasibility of using a smartwatch with children with ASD. Limitations of this study are addressed and implications for future research are posited.